Prospective evaluation of hematocrit in gender‐affirming hormone treatment: results from European Network for the Investigation of Gender Incongruence. (30th March 2018) - Defreyne, J.; Vantomme, B.; Van Caenegem, E.; Wierckx, K.; De Blok, C. J. M.; Klaver, M.; Nota, N. M.; Van Dijk, D.; Wiepjes, C. M.; Den Heijer, M.; T'Sjoen, G.
Summary: In trans persons on gender‐affirming hormonal treatment, a decrease (in trans women) or increase (in trans men) in hematocrit is often observed. Reference ranges for evaluation of hematocrit levels in trans persons have not been established. This prospective cohort study is part of the European Network for the Investigation of Gender Incongruence (ENIGI). At the Ghent and Amsterdam sites, we included 625 hormone‐naïve trans persons. Gender‐affirming hormonal treatment was initiated at the first visit. In trans men, serum hematocrit (Hct) levels increased during the first year (+4.9 Hct %, 95% CI 3.82–5.25), with the most pronounced increase during the first 3 months (+2.7 Hct %, 95% CI 1.94–3.29). Trans men receiving testosterone esters had a larger increase in serum hematocrit levels compared to trans men receiving testosterone undecanoate (Δ 0.8 Hct %). Of 192 trans men, 22 (11.5%) developed serum hematocrit levels ≥50.0%. Trans men on testosterone undecanoate were less likely to develop hematocrit levels ≥50% or ≥52%, compared to trans men on testosterone esters, and were less likely to develop hematocrit levels ≥50%, compared to trans men on testosterone gel. In trans women, serum hematocrit had dropped by 4.1 Hct % (95% CI 3.50–4.37) after 3 months, after which only small decreases were observed. In conclusion, serum hematocrit levels can be found in the reference range of the perceived gender as from 3 months after the initiation of gender‐affirming hormonal treatment.